Diagnostic accuracy of clinical and laboratory tests in scabies: A systematic review - Stefanie Kusuma; Alfin Harjuno Dwiputro (Published by Universitas Gadjah Mada, 2026)
Scabies is a highly contagious parasitic skin disease with significant global morbidity. Accurate diagnosis is essential for effective treatment and control; however, clinical manifestations are often nonspecific, and the performance of available diagnostic methods varies considerably. This systematic review synthesizes evidence on the diagnostic accuracy of clinical and laboratory-based tests for scabies. It followed PRISMA 2020 guidelines. A search of PubMed, Embase, and Web of Science was conducted between 2007 and December 2025 for studies evaluating the diagnostic accuracy of clinical diagnoses.skin scraping, adhesive tape testing, dermoscopy, and polymerase chain reaction (PCR). Eligible studies included human participants and reported sensitivity and/or specificity. Reference standards varied (clinical diagnosis, microscopy, skin scraping, dermoscopy). Two reviewers independently screened studies, extracted data, and assessed quality using QUADAS-2. When sufficient 2×2 data were available, specificity and predictive values were calculated. Due to heterogeneity, a narrative synthesis was conducted. Ten studies (2007–2025) involving 1,054 participants across Africa, Asia, Europe, and the Middle East were included. Skin scraping and adhesive tape testing demonstrated consistently high sensitivity, reaching up to 100% in studies using clinical diagnosis as the reference. Dermoscopy showed variable sensitivity (46–86%), influenced by operator expertise and patient factors. In studies with extractable data, dermoscopy versus microscopy yielded a specificity of 80.95%, with positive and negative predictive values of 84.0% and 85.0%. PCR showed high but heterogeneous sensitivity (74–100%), with improved performance using standardized sampling. Specificity reporting was inconsistent, limiting evaluation of false-positive rates. Skin scraping and adhesive tape testing remain the most sensitive diagnostic methods when mite material is present. Dermoscopy and PCR are useful complementary tools, though performance varies. An integrated diagnostic approach is recommended, and findings should be interpreted cautiously due to heterogeneity and variable reference standards.